Occupational and environmental acne - Penpun Wattanakrai (2018)
© Springer-Verlag Berlin Heidelberg 2000, 2012. Occupational and environmental acne includes oil acne, coal-tar and pitch acne, acne cosmetica, acne aestivalis (from sun), acne mechanica, tropical acne, and chloracne. Chloracne is a refractory acneiform eruption clinically characterized by comedones and straw-colored cysts. The comedones predominantly affect the malar region of the cheek and the retroauricular areas. Although chloracne is rare, it is a sensitive indicator of chemical exposure to certain polyaromatic halogenated hydrocarbons and may be associated with internal poisoning that should be recognized by physicians treating occupational skin disease. Patients with the cutaneous manifestations of chloracne should be carefully investigated for systemic complications (such as hepatic, ophthalmic, neurologic, lipoprotein, and endocrine abnormalities).